DYNAMIC AUTHORITIES ATTESTATION METHOD ZOROVO CHANNEL OPERATOR - Petrova , Yu. V. (Problems of Informatization and Management, 2021)
The methodology of a quick assessment of the operator is taught while being careful about the process.